Functioning Genome - Phenotype: the Contemporary View on Genetics - Rubikas, Jonas (Problemos, 2003)
Development of science has been marked by the points of methodological changes which oorrespond to the certain levels of investigation. Every level can be characterized by the object of investigation and the criterion of object evaluation which in genetics is the feature. The five methodological levels of investigation could be distinguished during the course of genetics deve- lopment: the organism - feature; the cell - feature; the chromosome - feature; DNA molecule - feature; nucleotide sequence - function. The methodology of the new level is genomics (DNA microarrays) and proteomes. Genomics is based on the DNA - DNA or DNA - mRNA hybridization; the thousands of molecules of individual genes (or all genes of a genome) can be analysed. Proteomes are based on two-dimensional electrophoresis of proteins. The thousands of proteins using very small amounts of protein mixture can be identified. The evaluation of results is performed by robots and computers. The genomics and proteomes as well as the data evaluation mark the beginning of the new methodological level: the functioning genome - phenotype.